Altering Compositional Properties of Viral Genomes to Design Live-Attenuated Vaccines - Pereira-Gómez, Marianoel; Carrau, Lucía; Fajardo, Álvaro; Moreno, Pilar; Moratorio, Gonzalo (Frontiers in Microbiology, 2021)
Live attenuated vaccines have been historically used to successfully prevent numerous diseases caused by a broad variety of RNA viruses due to their ability to elicit strong and perdurable immune-protective responses. In recent years, various strategies have been explored to achieve viral weakening by alternative routes to classical approaches based on successive passages in cell culture. A deeper understanding of evolutionary implications of distinct viral genomic compositional aspects, as well as substantial advances in synthetic biology technologies, has provided a framework to achieve new viral attenuation strategies. Herein, we will discuss different approaches that are currently being implemented to modify compositional features of viruses in order to attenuate them, leading to novel development of live attenuated vaccines.